Characterisation and functional analysis of the putative agr system in Clostridium acetobutylicum - Scott, Jamie (2012)
Clostridium acetobutylicum is an industrially important Gram positive organism which is capable of producing economically important chemicals in the Acetone, Butanol and Ethanol (ABE) process. An orthologue of the accessory gene regulator (agr) locus of Staphylococcus aureus has been found to be present in the genome of Clostridium acetobutylicum. In S.aureus, agr encodes a quorum sensing (QS) system that controls the expression of virulence in this species. Analysis of the agr region in C.acetobutylicum was conducted using reverse transcriptase PCR which showed the agrB and agrD genes to be linked. This was also the case with the agrC and agrA genes but there was no conclusive evidence to suggest that all 4 genes resided on the same operon. The use of cat-based reporter vectors which incorporate chloramphenicol acetyl transferase were used to look at the expression profiles of the agrB and agrC putative operons. The agrC construct showed activity consistent with the expected pattern of expression but this was not repeated with the agrB construct. Antisense RNA vectors were constructed with the intention of disrupting the agr genes but had no observable effect. This work was superseded by a newly available method to knockout the agrA gene by allelic exchange and the use of the ClosTron system to obtain gene inactivation in agrB, agrC and agrA. Gas chromatography analysis of these mutants showed little or no difference in product formation and a sporulation assay was developed which revealed that these mutants were inhibited in spore production. Finally, microarray analysis has been used to look at the effect of agrB inactivation on the gene expression of C.acetobutylicum. The expression of known sporulation genes was found to be differentially regulated. This study presents some of the first evidence to support the hypothesis that agr may be a major regulator in C.acetobutylicum and may act in a cell density dependent manner via a diffusible signal molecule.